Design And Construction of a Non-Contact Body Temperature Measuring Device Using the Mlx90614 Sensor Based on Nodemcu and the Blynk Application - Asni Tafrikhatin; Ajeng Tiara Wulandari; Juri Benedi; Intan Maharani (Politeknik Piksi Ganesha Indonesia, 2025)
Body temperature is an important indicator for monitoring a person's health condition. The average normal human body temperature ranges from 36–37°C. Changes in body temperature, whether hyperthermia or hypothermia, may indicate infections or metabolic disorders, making accurate and practical measurement methods essential. Conventional contact thermometers have limitations, such as long measurement times and user discomfort. To overcome these issues, a non-contact body temperature measurement system was designed using an infrared sensor. This sensor works by detecting thermal radiation emitted from the body’s surface without requiring direct skin contact. The device utilizes the MLX90614 infrared sensor, an ultrasonic sensor for distance detection, and a switch as an on/off control. Measurement results are displayed on an OLED screen and can be monitored via a smartphone through the Blynk platform. Based on testing, the non-contact body temperature measurement device achieved an accuracy level of 99.3%.